Different medicinal chemistry approaches towards the identification of novel targets in breast cancer - Pisano, Assunta; Bartolino, Roberto; Gabriele, Bartolo; Sindona, Giovanni; Maggiolini, Marcello (My University, 2013)
G protein-coupled receptors (GPCRs) belong to the largest family of cellsurface molecules representing the targets of approximately 40% of current medicinal drugs (Overington, J.P et al 2006). GPCRs are ubiquitous in mammalian (Bockaert, J. et al. 1999), regulate several physiological processes and play an important role in multiple diseases ranging from cardiovascular dysfunction, depression, pain, obesity to cancer (Rosenbaum D.M. et al. 2011). One member of this superfamily, named GPR30/GPER, mediates estrogen signaling in different cell contexts, leading to gene expression changes and relevant biological responses (Filardo E.J et al. 2000, Bologa C.G.et al. 2006, Maggiolini M. and Picard D. 2010). GPER acts by transactivating the Epidermal Growth Factor Receptor (EGFR), which thereafter induces the increase of intracellular cyclic AMP (cAMP), calcium mobilization and the activation of the phosphatidylinositol 3-kinase (PI3K) and the mitogen-activated protein kinases (MAPKs) (Maggiolini M. and Picard D. 2010). Moreover, the GPER-mediated transduction pathways activated by estrogens trigger the expression of a typical gene signature, including the expression of cfos and the gene encoding the connective tissue growth factor (CTGF), which are involved in the proliferation and migration of diverse cell types (Lappano R. et al 2012a, Madeo A. and Maggiolini M. 2010). On the basis of these findings, the first objective of the present study was the characterization of GPER from different points of view: GPERmediated signaling pathways and biological functions, selective ligands and molecular characterization of the receptors. In particular, the research project focused on:1. the transduction pathways by which the environmental contaminant Bisphenol A (BPA) influences cell proliferation and migration of human breast cancer cells and cancer-associated fibroblasts (CAFs); 2. the characterization of novel carbazole derivatives as GPER agonists in ER-negative breast cancer cells; 3. the isolation and characterization of GPER in estrogen-sensitive cancer cells by Mass Spectrometry. Additionally, the second section of this doctoral thesis was focused on the evaluation of the cytotoxic activity of novel synthesized compounds, given the interest and the need to discover new molecules against cancer. In particular, novel titanocene-complexes were studied evaluating their ability to elicit repressive effects on the growth of estrogen-sensitive breast cancer cells.
Scuola di Dottorato di Scienza e Tecnica "Bernardino Telesio", Organic Materials of Pharmaceutical interest XXVI Ciclo, a.a. 2012-2013
Keywords: Chimica organica; Chimica Farmaceutica; Recettori; Proteine